The Cell Wall Protein Ecm33 of Candida albicans is Involved in Chronological Life Span, Morphogenesis, Cell Wall Regeneration, Stress Tolerance, and Host–Cell Interaction - Gil-Bona, Ana; Reales-Calderon, Jose A.; Parra-Giraldo, Claudia M.; Martinez-Lopez, Raquel; Monteoliva, Lucia; Gil, Concha (Frontiers in Microbiology, 2016)
Ecm33 is a glycosylphosphatidylinositol (GPI)-anchored protein in the human pathogen Candida albicans. This protein is known to be involved in fungal cell wall integrity and is also critical for normal virulence in the mouse model of hematogenously disseminated candidiasis, but its function remains unknown. In this work, several phenotypic analyses of the C. albicans ecm33/ecm33 mutant (RML2U) were performed. We observed that RML2U displays the inability of protoplast to regenerate the cell wall, activation of the cell wall integrity pathway, hypersensitivity to temperature, osmotic and oxidative stresses and a shortened chronological lifespan. During the exponential and stationary culture phases, nuclear and actin staining revealed the possible arrest of the cell cycle in RML2U cells. Interestingly, a "veil growth", never previously described in C. albicans, was serendipitously observed under static stationary cells. The cells that formed this structure were also observed in cornmeal liquid cultures. These cells are giant, round cells, without DNA, and contain large vacuoles, similar to autophagic cells observed in other fungi. Furthermore, RML2U was phagocytozed more than the wild-type strain by macrophages at earlier time points, but the damage caused to the mouse cells was less than with the wild-type strain. Additionally, the percentage of RML2U apoptotic cells after interaction with macrophages was fewer than in the wild-type strain.